Uncovering the breeding contribution of transposable elements from landraces to improved varieties through pan-genome-wide analysis in rice - Li, Xiaoxia; Dai, Xiaofan; He, Huiying; Chen, Wu; Qian, Qian; Shang, Lianguang; Guo, Longbiao; He, Wenchuang (Frontiers in Plant Science, 2025)
IntroductionThe rice improvement process, driven by modern breeding techniques, represents the second revolutionary advancement in rice agronomic traits, following domestication. Advances in pan-genomes and enhanced capacity for analyzing structural variations have increasingly highlighted their role in rice genetic improvement. Transposable element (TE) variants have been previously reported to influence rice genomic diversity during the domestication, but their contribution to the improvement from landraces to improved varieties remains unclear.MethodsHere, we combined a high-quality pan-TE variation map, transcriptome profiles, and phenotypic data for 100 landraces and 92 improved varieties to investigate the contribution of TE variations to phenotypic improvement in rice.ResultsThe total number and length of TE variations in improved varieties were significantly greater than those in rice landraces, particularly for Ty3-retrotransposons, LTR Copia and Helitron elements. Comparing landraces and improved varieties, 4,334 selective TEs were detected within or near 3,070 genes that were enriched in basic metabolism and development and stress resistance. Among the 14,076 differentially expressed genes between the two groups, the expression level of 3,480 (24.7%) genes were significantly associated with TE variations. Combining with haplotype analysis, we demonstrated potential patterns of how TEs affect gene expression variation and thereby participate in the improvement of important agronomic traits in rice.DiscussionCollectively, our results highlight the contributions of TE variations to rice improvement in shaping the genetic basis of modern rice varieties and will facilitate the exploration of superior genes and advance molecular breeding efforts in rice.